HADIS PERSPEKTIF MUHAMMAD AL-GHAZALI - Sutrisno Sutrisno (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2017)
The very prominent figure reinforcing the understanding of the hadith, and being the basis of the assessment of the hadith of the Prophet is Muhammad al Ghazali, for him in understanding the hadith, not only to know the material of hadith but more important is to know how he delivered it and with whom he spoke, for Rasulullah in his life sometimes acts as an ordinary human being, as a person, as husband, as the messenger of Allah, as head of state, as community leader, as commander or judge. According to Muhammed Al Ghazali there are five criteria of the authenticity of hadith, three related to sanad and two criteria related to matan, in practicing the study of hadiths it is necessary to cooperate among the hadith experts with various other experts, including jurisprudence, tafsir, ushul fiqh and kalam experts. Given the material hadith there is to do with aqeedah, worship and muamalah so require knowledge from various experts.